2021
DOI: 10.3389/fbioe.2021.761218
|View full text |Cite
|
Sign up to set email alerts
|

Nanosonosensitizers With Ultrasound-Induced Reactive Oxygen Species Generation for Cancer Sonodynamic Immunotherapy

Abstract: Immunotherapy is a promising therapeutic strategy for cancer, while it has been demonstrated to encounter the issues of low immune responses and underlying immune-related adverse events. The sonodynamic therapy (SDT) that utilizes sonosensitizers to produce reactive oxygen species (ROS) triggered by ultrasound (US) stimulation can be used to ablate tumors, which also leads to the induction of immunogenic cell death (ICD), thus achieving SDT-induced immunotherapy. Further combination of SDT with immunotherapy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Calreticulin (CRT) exposure on the cell membrane and damage‐related molecular patterns (DAMPs) secreted from the cell, including high mobility group box 1 (HMGB1), are considered as commonly used detection factors for ICD. [ 23 ] The CRT exposure on the surface of B16‐F10 cells was assessed by immunofluorescence confocal microscopy. The results revealed that Ru‐TePt@siRNA‐MVs + US group induced higher levels of CRT exposure on the cell surface than the untreated group (Figure S17, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Calreticulin (CRT) exposure on the cell membrane and damage‐related molecular patterns (DAMPs) secreted from the cell, including high mobility group box 1 (HMGB1), are considered as commonly used detection factors for ICD. [ 23 ] The CRT exposure on the surface of B16‐F10 cells was assessed by immunofluorescence confocal microscopy. The results revealed that Ru‐TePt@siRNA‐MVs + US group induced higher levels of CRT exposure on the cell surface than the untreated group (Figure S17, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Owing to SDT can generate intracellular ROS to induce ICD, immunofluorescence staining of CRT in MC38 cells, a common ICD marker that could stimulate antigen presentation and induce immune response ( 19 , 20 ) was conducted. As shown in Figure 3D and Supplementary Figure 2C , cells treated with nanodrugs alone or US irradiation alone exhibited negligible green fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, some emerging ablation technologies are also exploring the possibility of combining with immunotherapy. For example, after photodynamic therapy, various immune cells, including T cells, DCs, neutrophils, NK cells and macrophages are activated, Treg cells are increased and PD-L1 expression is up-regulated ( 46 ).At the same time, sonodynamic therapy can trigger systemic immune responses by eliciting ICD and repolarize macrophages from immunosuppressive M2 to antitumor M1 phenotypes ( 60 ). Which indicates that the combination of dynamic therapy and immunotherapy is a good strategy.…”
Section: Discussionmentioning
confidence: 99%